(untitled) (International Journal of Contemporary Security Studies, 2021)
History of imprisonment has been conceived and organised in a variety of ways. Reformers tried to shape the prison regime to suit their purposes, but the reality of the prison system displayed the substantial limits of their achievements (for example high costs for construction of prisons; level of criminality, minimum protection of future victims etc.). In the second half of the 20th century, a search for new ways of solutions of criminality and penal policy begins. The idea of a restorative prison exists at the moment in concept only. This concept is based on the opportunities for prisoners to encounter their actual victims for restorative dialogue. Restorative programs also enhancing the return of prisoners into family environment and community and improve a dynamic security in prison.